2019
DOI: 10.5455/medarh.2019.73.399-403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cesarean Section and Analysis of Neonatal Apgar Score and the Mean Time of Second Phase of Labor in Pregnant Women

Abstract: Introduction: The labor pain is probably the most severe pain a mother experiences in her lifetime and is usually severe and prolonged in women with pregnancy, Aim: To evaluate the effects of labor epidural and spinal analgesia on the incidence of cesarean section in painless delivery. Methods: This randomized clinical trial was conducted on pregnant women aged 37-42 weeks of pregnancy. Female candidates for painless labor were divided into two groups: Epidural Analgesia (EA) and Spinal Analgesia (SA). Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Dalam persalinan tanpa rasa sakit, tujuan seperti penurunan tingkat operasi caesar, peningkatan kecenderungan untuk persalinan normal, relaksasi mental selama persalinan yang sulit diikuti. Dalam hal ini, persalinan tanpa rasa sakit dinegara kita dapat menjadi alternatif yang baik untuk operasi Caesar yang tidak professional (Shokrpour, Reza, Sharifi, & Kamali, 2019).…”
Section: Pendahuluanunclassified
“…Dalam persalinan tanpa rasa sakit, tujuan seperti penurunan tingkat operasi caesar, peningkatan kecenderungan untuk persalinan normal, relaksasi mental selama persalinan yang sulit diikuti. Dalam hal ini, persalinan tanpa rasa sakit dinegara kita dapat menjadi alternatif yang baik untuk operasi Caesar yang tidak professional (Shokrpour, Reza, Sharifi, & Kamali, 2019).…”
Section: Pendahuluanunclassified
“…Cesarean section (CS) is an obstetric surgery normally performed when vaginal delivery may compromise the well-being of mother and/or neonate [1]. Its prevalence went beyond the limit (10-15%) recommended by World Health Organization (WHO) [2], and reached 32% [3,4], even 46%, [5]. Prevalence exacerbation is due to the performed CS upon request, of some mothers whose reasons include pain fear of normal vaginal delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches showed that more than 32% [35% in USA [1] ;32,5 in Ethiopia, Africa [2] , 32% in Thailand [3] of women, give birth under cesarean section [CS]. The trend is increasing [1] and even reached 46% in China according to the results of a study published in 2016 [4] . Many cesarean deliveries [CD] are performed under neuraxial anesthesia using local anesthetics [LAs] [2] .…”
Section: Introductionmentioning
confidence: 99%